Identificación y evaluación de los riesgos psicosociales con la aplicación del test de navarra aplicado a los trabajadores de losep y sindicalizados de la Universidad Técnica de Cotopaxi - Berrones Baque, Naile Carolina (2016)
The institutions of Higher Education and Society, is currently undergoing a process of transformation of labor and business. This transformation leads to new job demands that become psychosocial factors risks so that the proposed project was developed as a means to identify, understand, and know the psychosocial issues that most influence within the institution, that affect the health of workers. The present researching work was developed at Technical University of Cotopaxi by means of the identification and evaluation of psychosocial risks in the institution through a Navarra Test, we achieved to know what are the factors with more influence in the average physical-friendly organization. The research shows and determines the qualification, psychosocial risks and estimate the measures propose to control and mitigate the factors which affect the healthy life in the workers of the institution.